Alternative Dispute Resolution for Consumer Cases: Are Divergences an Obstacle to Effective Access to Justice? - Urša Jeretina; Alan Uzelac (Central European Public Administration Review)
Traditional court proceedings do not always offer practical and cost-appropriate way of resolving consumer disputes. Some authors consider that, in disputes between consumers and businesses, alternative dispute resolution (ADR) is more effective, faster and cheaper. Insofar, consumer ADR (CADR) is seen as a useful instrument that helps consumers realize their right of access to justice. It is argued that the CADR is a flexible and faster method of enforcement of consumers’ rights, and that CADR systems provide valuable information on the needs of applicants, while preserving confidentiality and increasing consumer satisfaction. However, while praised in theory, the CADR in real life has not reached the desired levels. It seems that both sides, businesses and consumers, lack awareness of ADR schemes and their benefits. In this paper we analyze the concept of CADR through compensatory collective redress, and explore whether current legal initiatives of the European Union (EU) are ultimately contributing to increasing consumer confidence in the internal market of the EU Member States. Special attention is paid to different barriers for the development of various ADR schemes. They are reflected not only in different ADR schemes, but also in the evaluation methods used to measure efficiency of the use of the (C)ADR. The EU Directive on Consumer ADR and Regulation on Online Dispute Resolution (ODR) have attempted to set flexible rules that would assure quality of dispute resolution between entities in the EU. However, the EU initiatives so far leave many questions unanswered, in particulars the questions about supervision and financing of consumer ADR schemes, as well as the issues regarding purely internal harmonization of CADR practices. An example for considerable divergences are CADR proceedings in the neighboring Western Balkan states, such as Slovenia and Croatia.